KARDINALE ASPEKTE VAN NASIONALE DIENSPLIG MET SPESIFIEKE VERWYSING NA SUID-AFRIKA - Nöthling, C.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
This article reviews the cardinal aspects of universal military service (conscription) with specific reference to the South African situation, and against the backdrop of military service in what the author terms as the 'international community'. In his introduction he discusses the evolution of compulsory military service in the briefest terms, and then proceeds to a comparative overview of the subject within the international framework. It is averred that military service in most Western countries (and especially those in NATO) compares most unfavourably with induction in the forces of Warsaw and the Peoples' Republic of China. There are a few notable exceptions, however, viz Switzerland (which pursues an effective policy of armed neutrality), Israel and the Republic of South Africa. Comparing the 'average' Soviet and South African soldier, he concludes that while the Russian counterpart is the submissive product of an austere system, the South African soldier is a more balanced combination of self-discipline and initiative. This implies that even the military system is only fractional, and to a large extent reflects the rules of society. On this premise he takes a closer look at National Service as a system influenced by the community. In this respect attention is given to four cardinal aspects, viz economy, age groups, military dissenters and volunteers. Although accepting the notion of critics that the national economy in South Africa could be adversely affected by (any) system of extended service, he claims - with historical inference - that the new system will alleviate the individual's obligations. The part dealing with the induction of older men is a brief study in comparative history and carries the notion that not only young men can play the game called 'war'. The author views the growing phenomenon of military dissent (or resistance to military service) in the Western countries with concern, and comments that this pacifist attitude can and will be exploited by radical movements with political objectives. This is the case with organizations such as the South African Liberation Support Committee (SALSCOM) which aims to undermine the South African Defence Force, thereby paving the way for a communist take-over in the Republic of South Africa. As to the final aspect, viz volunteers, the view is expounded that in the face of an external threat (or in actual conflict) no country can rely on a system of voluntary military service. In his final analysis the author concludes that as the calibre of men produced by a particular military system is always an indication of the efficiency of such a system, National Service in South Africa should be judged in positive terms: the South African soldier, being a product 0: an effective military system, ranks among the best in the world.